Miniaturized HTS linear phase filter based on neighboring CQ units sharing resonators. (3rd September 2015) - Zhang, Tianliang; Yang, Kai; Zhu, Hai; Zhou, Liguo; Jiang, Mingyan; Dang, Wei; Ren, Xiangyang; Hou, Fangyan
Abstract: This paper presents a method for using neighboring cascaded quadruplet (CQ) units sharing resonators to decrease the order of filter so as to reduce the size of a high temperature superconducting (HTS) linear phase filter. The main advantage is that it will not reduce the number of the filter's transmission zeros, and will not increase the difficulty of circuit design and tuning. Based on this method, this paper presents a 10-order HTS linear phase filter with two pairs of transmission zeros on double-sided YBCO/LaAlO3 /YBCO films with a size of 20.3 mm × 20.92 mm, a thickness of 0.5 mm and a dielectric constant of 24.04. At 77 K, the filter's measured center frequency is 830.03 MHz with a bandwidth of 10 MHz, an edge out-of-band rejection greater than 30 dB MHz −1, and a group delay variation of less than ±10 ns over 60% of the filter bandwidth.